Report of the Committee on the Peaceful Uses of Outer Space Fifty-Seventh Session (11-20 June 2014) - United Nations (United Nations, 2014)
This is the official report of the Committee on the Peaceful Uses of Outer Space on the fifty-seventh session held in Vienna from 11 to 20 June 2014.